2017
DOI: 10.1155/2017/6451963
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Comparison of 20(R)‐ and 20(S)‐Ginsenoside Rh1 and 20(R)‐ and 20(S)‐Ginsenoside Rg3 in Rat Plasma following Oral Administration of Radix Ginseng Rubra and Sheng‐Mai‐San Extracts

Abstract: Ginsenosides Rh1 and Rg3, as the main bioactive components from Ginseng, are effective for prevention and treatment of cardiovascular diseases. Sheng-Mai-San (SMS), a classical complex prescription of traditional Chinese medicines, is composed of Radix Ginseng Rubra, Fructus Schisandrae, and Radix Ophiopogonis. In this research, a sensitive and specific liquid chromatography-mass spectrometric method was developed and validated for stereoselective determination and pharmacokinetic studies of 20(R)- and 20(S)-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…[ 26 ] KYU'S and Xiaomei Fan demonstrated RG can modulate antioxidant enzymes, which has biochemical and functional effects for the heart. [ 27 , 28 ] Studies have shown that Radix Aconiti Lateralis Preparata and its active component can improve left ventricular systolic and diastolic function, which is of great importance to improve chronic HF. [ 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] KYU'S and Xiaomei Fan demonstrated RG can modulate antioxidant enzymes, which has biochemical and functional effects for the heart. [ 27 , 28 ] Studies have shown that Radix Aconiti Lateralis Preparata and its active component can improve left ventricular systolic and diastolic function, which is of great importance to improve chronic HF. [ 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…Various methods were developed for studying pharmacokinetics of complex mixtures. High-pressure liquid chromatography mass spectrometry techniques (HPLC MS) can be used for specific and sensitive detection of individual active compounds in blood plasma, taking into account their stereochemistry [ 23 ]. Different modifications of HPLC MS allow for simultaneous detection of up to ten individual components of plant extracts in biological samples [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Rg3 has been studied for the different efficacy of two forms. (Kwok et al, 2012;Fan et al, 2017;}. Among many ginsenoside saponins, Rg3 is well known in the public, but not much research has been done, such as Rb1, Rg1, and Rb2.…”
Section: Introductionmentioning
confidence: 99%